Variabel-Variabel yang Mempengaruhi Intensitas Merokok Remaja Pria di Indonesia Tahun 2017 - Vivy Maharani; Titik Harsanti (Politeknik Statistika STIS, 2021)
Indonesia is the country with the third largest number of cigarette smokers in the world. Cigarette smokers are dominated by males smokers. However, many smokers are adolescent. Smoking will cause great addiction in adolescence. The addictive substances contained in cigarettes will interfere brain development. This paper analyzes the cigarette smoking intensity determinants and their tendencies among males adolescents in Indonesia in 2017. The analisys use secondary data from the 2017 Indonesian Demographic and Health Survey (IDHS),with male adolencents smokers aged 15-24 years as the unit of analysis. Data were analyzed using ordinal logistic regression analysis. The results show that school status, work status, radio access, household economic status, age, and the cigarette smoke exposure in the house, were significantly affected the cigarette smoking intensity of males adolescent. These findings suggest that education about danger caused by cigarette smoking for children should be given as early as possible.